2009
DOI: 10.1111/j.1532-5415.2008.02147.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effect on Mortality of a Home Intervention that Reduces Functional Difficulties in Older Adults: Results from a Randomized Trial

Abstract: Objectives-To evaluate long-term mortality effects of a home-based intervention previously shown to reduce functional difficulties, and whether survivorship benefits differed by risk level.Design-Two-group randomized trial with survivorship followed up to 4 years from study entry. Setting-Homes of urban community-living elders.Participants-319 adults 70+ years with difficulties performing daily activities.Intervention-Occupational and physical therapy sessions to instruct participants in compensatory strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 30 publications
0
65
0
1
Order By: Relevance
“…The tailored intervention program is based on the "Advancing Better Living for Elders" program (ABLE) (Gitlin et al, 2009;Gitlin et al, 2006). It is a homebased intervention program including individually developed rehabilitation plans for each patient.…”
Section: Study Contextmentioning
confidence: 99%
“…The tailored intervention program is based on the "Advancing Better Living for Elders" program (ABLE) (Gitlin et al, 2009;Gitlin et al, 2006). It is a homebased intervention program including individually developed rehabilitation plans for each patient.…”
Section: Study Contextmentioning
confidence: 99%
“…An initial paper demonstrated that individuals who received the intervention had better perceived capabilities in ADL, IADL, greater self-efficacy and less fear of falling than individuals in the control group both immediately and six months after receiving the invention (Gitlin et al, 2006a). The current paper (Gitlin et al, 2009) is the second report on the survival of participants. In the first, significantly better survival among members of the intervention group was noted at 14 months follow-up (Gitlin, Hauck, Winter, Dennis & Schulz, 2006b).…”
Section: Commentarymentioning
confidence: 83%
“…1–3 A home evaluation and fall reduction program has shown decreases in mortality 2 years after intervention. 4 …”
Section: Introductionmentioning
confidence: 99%